The false promise and bitter fruit of Neoliberalism - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2022)
Neoliberalism is a political economic philosophy that consists of two claims, one economic and the other political. The economic claim is free market laissez-faire economies are the best way to organize economic activity as they generate efficient outcomes that maximize well-being. The political claim is free market economic arrangements promote individual liberty. This paper argues both claims are problematic. The evidence from the forty-year experiment that began in 1980 shows Neoliberalism has undercut shared prosperity and unleashed illiberal forces that threaten liberty. The paper distinguishes between the first political turn which saw the establishment of Neoliberal political hegemony, and the second political turn toward proto-fascism that we are now experiencing. The second turn is being driven by a collection of factors which have created a demand for proto-fascism and weakened the defenses against alt-right ideas. Those factors include socio-economic disembedding, institutional destruction and political disembedding, increased economic inequality that tilts political power, transformation of attitudes to government and governance, transformation of economic identity, and cultural transformation that celebrates sociopathic egotism. The Third Way's capture of center-left politics means liberal elites occupy the political place that should be held by true opponents of Neoliberalism. Those liberal elites obstruct the politics needed to reverse the deep causes of the drift to proto-fascism. Ironically, that makes those elites a real danger.
Keywords: P1; P16; 330; Neoliberalism; proto-fascism; disembedding; inequality; power; culture